2004
DOI: 10.1177/1545968304271171
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Muscle Strength and Integration of Afferent Input to Postural Instability in Persons with Stroke

Abstract: Objectives-To determine the relationship of muscle strength to postural sway in persons with stroke under standing conditions in which vision and ankle proprioception were manipulated.Methods-Forty persons with stroke and 40 healthy older adult controls were recruited from the community and underwent balance testing consisting of six conditions that manipulate vision and somatosensory information while standing. Postural sway was measured during each condition. In addition, lower extremity joint torques and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
4
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 27 publications
1
77
4
6
Order By: Relevance
“…Although a stroke patient may survive with appropriate first aid and early treatment after the initial symptoms, stroke symptoms such as impairment of motor and sensory function, cognition, balance, and gait often persist 2) . Asymmetrical posture and weight bearing are the most common post-stroke symptoms, causing an increase in postural sway 3) . The increase in postural sway during standing is due to the degeneration of the nervous system and is more severe in elderly people than young adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a stroke patient may survive with appropriate first aid and early treatment after the initial symptoms, stroke symptoms such as impairment of motor and sensory function, cognition, balance, and gait often persist 2) . Asymmetrical posture and weight bearing are the most common post-stroke symptoms, causing an increase in postural sway 3) . The increase in postural sway during standing is due to the degeneration of the nervous system and is more severe in elderly people than young adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bowen et al 11) confirmed that stroke patients show increased anteroposterior postural sway when visual input is blocked in a standing posture. Furthermore, when integrating the sensory information in the central nervous system (CNS) for postural control, postural sway increases due to damage in the proprioception processing center in the upper spinal cord 3) . To investigate the influence of proprioception on postural sway for stroke patients in a sitting posture, van Nes et al 12) compared the difference in postural sway between sitting on stable and unstable surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bonan IV et al [20] reported that parameters of posture stability in stroke patients were significantly lower than those from normal subjects. Marigold DS et al [21] reported that postural sway was increased in the stroke group.…”
Section: Discussionmentioning
confidence: 96%
“…These patients suffer from impairment in static and dynamic balance [6] and have a high records of falling [3][4][5]. Stability in standing and walking is controlled by musculoskeletal, somatosensory, and vestibular systems [7][8][9][10]. Based on the results of various studies, stroke subjects are unable to control their standing balance and are at risk of falling [6,11,12].…”
Section: Introductionmentioning
confidence: 99%